Dendrimers as Carriers for siRNA Delivery and Gene Silencing: A Review - Jiangyu Wu; Weizhe Huang; Ziying He (The Scientific World Journal)
RNA interference (RNAi) was first literaturally reported in 1998 and has become rapidly a promising tool for therapeutic applications in gene therapy. In a typical RNAi process, small interfering RNAs (siRNA) are used to specifically downregulate the expression of the targeted gene, known as the term “gene silencing.” One key point for successful gene silencing is to employ a safe and efficient siRNA delivery system. In this context, dendrimers are emerging as potential nonviral vectors to deliver siRNA for RNAi purpose. Dendrimers have attracted intense interest since their emanating research in the 1980s and are extensively studied as efficient DNA delivery vectors in gene transfer applications, due to their unique features based on the well-defined and multivalent structures. Knowing that DNA and RNA possess a similar structure in terms of nucleic acid framework and the electronegative nature, one can also use the excellent DNA delivery properties of dendrimers to develop effective siRNA delivery systems. In this review, the development of dendrimer-based siRNA delivery vectors is summarized, focusing on the vector features (siRNA delivery efficiency, cytotoxicity, etc.) of different types of dendrimers and the related investigations on structure-activity relationship to promote safe and efficient siRNA delivery system.